Consumption of processed and ultra-processed products and their impact on adult health (Research, Society and Development, 2021)
The daily life of modern life has demanded more practicality and agility in routine activities, also affecting people's diet, in terms of food choice. In this sense, processed and ultra-processed products have gained prominence in consumption, either because of the ease and reduction in the time to prepare these foods. One of the problems surrounding high consumption is the triggering of Chronic Non-Communicable Diseases, such as diseases of the gastrointestinal tract, cardiovascular disease, obesity and metabolic disorders. Therefore, the aim of this study was to analyze the impact of consumption of processed and ultra-processed products on the health of adults. For this, an integrative literature review was carried out, in the time frame between 2011 and 2021 and with results on the growth of food industries, high consumption of these foods, their classification and the negative impacts they bring to adulthood. So, the conclusions highlight the importance of raising awareness among the population around the issue, the harm to the body, which can be avoided in a simple way, such as replacing it with healthy foods.